Odpowiedzi

2010-02-28T15:09:08+01:00
A)
V= a³
V = ( 5cm) ³
V= 125 cm³

P= 6a²
P= 6 * ( 5cm) ²
P= 150 cm²

b)
V= (1,4 dm) ³
V= 2,744 dm ³

P= 6 ( 1,4 dm) ²
P= 11, 76 dm²

c)
V= (0,3 m) ³
V= 0,027 m³

P= 6 * ( 0,3 dm) ²
P= 0,54 dm²
1 5 1
Najlepsza Odpowiedź!
2010-02-28T15:10:47+01:00
P - 6* a*a
V - a*a*a
a) P - 6 * (5cm *5cm) = 6* 25cm = 150cm(kwadratowych)
V - 5cm*5cm*5cm = 25cm * 5cm = 125cm(sześciennych)
B)6 * ( 1,4dm *1,4dm ) = 6*1.96=11.76dm(kwadratowych)
V - 1,4 * 1,4*1,4 = 1.96 * 1.4 = 2.744dm(szesciennych)
c)P - 6 * 0,3*0,3 = 6* 0.09=0.54m(kwadratowych)
V - 0,3*0,3*0,3 = 0.09*0,3=0,027m(szesciennych)
1 5 1